Evaluation of the Effect of Changing Concentration and pH on The Activity of Rose Bengal Antigen - Muthanna I. Al-Ezzi (College of Pharmacy / Mustansiriyah University, 2009)
The present study was conducted to prepare Rose Bengal antigen by using Rose Bengal stain 1% and brilliant green 0.5%. These antigens were prepared using different concentrations (4%, 5%, 6%, 7%, 8%, 9% and 10%) and different buffer diluents with different pH (3.0, 3.5, 3.65, 4, 4.5, 5.0) to study the effect of different antigen concentrations and pH on the Rose Bengal test. It was observed that the best results were obtained when the concentration of the antigen was more than 7% and the pH range of 3.65 to 4.0.